Cele programowe partii nacjonalistycznych w Europie na początku XXI wieku. Przykład Front National (Rassemblement National), Nationaldemokratische Partei Deutschlands i Ruchu Narodowego = The program goals of nationalist parties in Europe at the beginning of the 21st century. Example of the National Front (the National Rally), the National Democratic Party of Germany and the National Movement - Malendowicz, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article are the goals of nationalist political parties included in their political programs. The political programs of selected nationalist parties operating in France, Germany and Poland were analyzed. The aim was to answer the question about the content of the programs and its adequacy to the changes taking place in the modern world and related to European integration,globalization understood as unification, uniformization and standardization, as well as the concepts oforganization of societies in the analyzed countries and deficits of democracy at the supranational level.
Keywords: nacjonalizm; radykalizm; partie polityczne; program polityczny; Front Narodowy; Narodowodemokratyczna Partia Niemiec; Ruch Narodowy; globalizacja; integracja europejska; nationalism; political party; radicalism; political program; National Front; National Democratic Party of Germany; National Movement; globalization; European integration